Practices of caregivers when evaluating the risk of falls in the admission of older adults to nursing homes - Baixinho, Cristina Lavareda (2021)
Falls are a complex problem for the older population residing in nursing homes. Despite recommendations, many difficulties remain in the evaluation of and systematic information on fall risk factors.